2022
DOI: 10.1155/2022/1842389
|View full text |Cite|
|
Sign up to set email alerts
|

Curcumin Inhibits the Proliferation of Renal Cancer 786-O Cells through MTOR Signaling Pathway and Its Mechanism

Abstract: Objectives. The mechanism of curcumin inhibiting renal cancer 786-O cells proliferation through MTOR signaling pathway was investigated. Methods. Human renal cancer 786-O cells were cultured with curcumin for 48 h. The OD values were measured by the MTT method, and the growth inhibition rate of 786-O cells was calculated. The cell cycle distribution and apoptosis rate were detected by flow cytometry (FCM). Transwell chamber was introduced to detect cell invasion ability. Cell migration ability was detected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%